Abutting Left Atrial Appendage and Left Superior Pulmonary Vein Predicts Recurrence of Atrial Fibrillation After Point-by-Point Pulmonary Vein Isolation - Szegedi, Nándor; Simon, Judit; Szilveszter, Bálint; Salló, Zoltán; Herczeg, Szilvia; Száraz, Lili; Kolossváry, Márton; Orbán, Gábor; Széplaki, Gábor; Nagy, Klaudia Vivien; Mahdiui, Mohammed El; Smit, Jeff M.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The role of the spatial relationship between the left superior pulmonary vein (LSPV) and left atrial appendage (LAA) is unknown. We sought to evaluate whether an abutting LAA and LSPV play a role in AF recurrence after catheter ablation for paroxysmal AF. Methods: Consecutive patients, who underwent initial point-by-point radiofrequency catheter ablation for paroxysmal AF at the Heart and Vascular Center of Semmelweis University, Budapest, Hungary, between January of 2014 and December of 2017, were enrolled in the study. All patients underwent pre-procedural cardiac CT to assess left atrial (LA) and pulmonary vein (PV) anatomy. Abutting LAA-LSPV was defined as cases when the minimum distance between the LSPV and LAA was less than 2 mm. Results: We included 428 patients (60.710.8 years, 35.5% female) in the analysis. AF recurrence rate was 33.4%, with a median recurrence-free time of 21.2 (8.8-43.0) months. In the univariable analysis, female sex (HR=1.45 95%CI=1.04-2.01 p=0.028), LAA flow velocity (HR=1.01; 95%CI=1.00-1.02; p=0.022), LAA orifice area (HR=1.00; 95%CI=1.00-1.00; p=0.028) and abutting LAA-LSPV (HR=1.53 95%CI=1.09-2.14 p=0.013) were associated with AF recurrence. In the multivariable analysis, abutting LAA-LSPV (adjusted HR=1.55 95%CI=1.04-2.31 p=0.030) was the only independent predictor of AF recurrence. Conclusion: Abutting LAA-LSPV predisposes patients to have a higher chance for arrhythmia recurrence after catheter ablation for paroxysmal AF.